Primary Caregivers of Patients with Psychoactive Substance Use Often Suffer from Depression & Anxiety - Muhammad Umar Marri, Zainullah Khan, Ali Ahsan Mufti, Zarmina Tareen, Asif Kamal, Ejaz Gul, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of depression and anxiety in carers of psychoactive substance use patients. Study Design: Cross sectional study Place and Duration of Study: Department of Psychiatry, Baluchistan Institute of Psychiatry & Behavioural Sciences, Quetta from June 2020 to December 2020. Methodology: One hundred and twenty caregivers of psychoactive substance use patients were enrolled. Detailed demographics of patients and caregivers were recorded after taking informed written consent. Patients were aged between 18-70 years. Depression and anxiety were calculated in primary caregivers of patients of psychoactive substance use. A DASS-21 criterion was used to examine the depression. Data was analysed by SPSS 22.0. Results: Mean age of patients was 35.27±15.43 years. 90 (75%) patients were males while 25% were females. Among caregivers 78 (65%) were females while 42 (35%) were males with mean age 36.86±16.48 years. Among caregivers, 12.5% of the patients had mild, 37.5% showed moderate and 18.33% caregivers showed severe depression while 38 (31.67%) had no depression. Anxiety among caregivers was mild in 12 (10%), 26 (21.7%) had moderate and 15 (12.5%) caregivers had severe anxiety while 67 (55.83%) caregivers had no anxiety. Conclusion: The frequency of anxiety and depression was high in primary caregivers of patients with psychoactive substance abuse. Keywords: Anxiety, Depression, Substance use, Caregivers